Gerenciamento proteano de carreira entre universitários - Borges, Ludmila Ferreira Liberato (2014)
From the second half of the twentieth century, changes in the capitalist way of production began to affect the relationship that companies established with workers. Facing an unpredictable market, the traditional career, characterized, among other aspects, by lasting jobs and opportunity for advancing in the organization hierarchy, has become less recurrent. Simultaneously, new conceptions of career began to emerge, most of which with an individualistic approach. Among other studies, this paper used as a reference the protean career study. This model, proposed by North American scholars, focuses on the concept of a career that is managed by the individual who aims to achieve psychological success. Thus, it is anchored in two main dimensions: self-directedness and values-driven. Considering the several studies describing the difficulties faced by students during the transition from university to the labor market, this research aimed at understanding the aspects of protean career management among Brazilian students who had completed, at least, the first half of an undergraduate course. The study was divided into two articles. The first aimed at developing and validating the Protean Career Attitude Scale for undergraduates and was conducted with a sample of 1,016 students from 37 different courses, ranging in age between 18 and 65 years old, with an average of 25.52 (SD = 6.69 years). The instrument, in this study, was called the Protean Career Management Scale for Undergraduate Students, and it verified the two-dimensional structure, also found in the original version of the measuring process. The reliability index was satisfactory and higher than .61, being possible to be used in services of professional or career counseling. The second paper aimed at understanding how the 14 dimensions of the protean model relate to sociodemographic variables and psychosocial constructs: personality, locus of control, health and life satisfaction. It involved 245 students enrolled in Humanities courses and 280 enrolled in Natural Sciences courses. The total consisted of 525 students, out of which 52% were male ones. The age of participants ranged from 18 to 30 years, and an average of 22.59 years (SD = 2,66. years). Based on the results of study 2, it was found that Humanities students tend to have a higher average in the values-driven dimension than the Natural Sciences students. It was also found that the aspects of conscientiousness and internal control of locus are significant predictors of self-directedness, both among Humanities and Natural Sciences students. It was also found that the adoption of protean attitudes tend to positively impact health and life satisfaction aspects of the subject. In general terms, the study also allowed the identification of protean characteristics among university students, as it also made possible to find out the variables related to attitudes of self-directedness and values-driven. However, it must be pointed out that further research must be carried out on other psychosocial variables that may be related to protean career management among university students.